Data Life-Cycle Management Project: SUC P2 2015-2018 - Blumer, Eliane; Burgi, Pierre-Yves (Revue électronique suisse de science de l’information (RESSI), 2015)
This text is about the Swiss University Conference (SUC) program 2 (P2) project entitled “data life-cycle management” (DLCM), which is partnered with library-, IT-, research-, and/or Life Sciences and Digital Humanities-departments from eight Swiss Higher Education Institutions (EPFL, HEG / HES-SO, UNIL, UNIBAS, UNIZH, ETHZ, UNIGE and SWITCH). The project, accepted in August 2015, aims at offering services to the Swiss research community to help them manage their research data more conveniently. Herein, after introducing the research data management topic, we present the methodology and organization of such a comprehensive project, starting by collecting researchers’ opinions, expressing them into needs, and ending with a detailed description of what the already existing and future outcomes of the project will be, in 2018.